Comparative analysis of measurements accuracies that acquires from DGPS and Total Station (The International Journal for Scientific Research, 2025)
Surveying and geodesy are vital technical fields that play a crucial role in achieving progress and development in various sectors, such as civil engineering, construction, energy, transportation, and many others. The research aims to choose the optimal method for field surveying. To achieve this goal, it was necessary to conduct a number of field observations, including measuring the coordinates of a number of ground points using surveying devices, then comparing the results using statistical methods.Two types of surveying devices were used during observations operations, one of which was the Total Station Leica TS07 and the other device was Differential GPS. Leica for the same observed points. Through cadastral projection of the corners of the buildings, the results were compared. It was found that there were slight differences in field measurements. In this research paper, the Northern Technical University stadium was chosen as a study area because the stadium contains ground control points. Monitoring work began using a differential GPS device and included surveying and mapping, followed by setting out work using a total station device. The statistical results obtained by the Total Station and GNSS technology in observation revealed the superiority of the second type in terms of the (RMSE) value for the three ground coordinates.
Keywords: GPS; Total Station; Coordinates; Accuracy